Empowerment and Education on Family Medicinal Plants to Support Traditional Medicine in Dasa Wisma Gropus RT 31 and RT 33, Sungai Dama Village, Samarinda Ilir District - Sepsamli, Letus; Hidayat, Imam; Alisha, Gesha Desy; Dirna, Fitria Cita; Mondina, Resta Rene; Syarifudin, Achmad (Keris: Journal of Community Engagement, 2025)
Urban communities plant more ornamental and vegetable crops than medicinal plants, although medicinal plants are one solution for maintaining health and supporting the treatment of illnesses within the family. There are many types of family medicinal plants useful in curing diseases that can be grown in the home garden or on the terrace. This community service aims to increase the knowledge of Dasa Wisma mothers in RT 31 and RT 33, Sungai Dama Village, about the types of family medicinal plants and to increase their knowledge of how to process and use family medicinal plants. The method applied in this service is lectures to educate about family medicinal plants, their processing, and their use. There were 35 Dasa Wisma participants. Based on the observation results, this service has a positive impact because the mothers actively asked questions during the discussion session after the material was presented. The Dasa Wisma mothers asked for more detailed information about how to process and use family medicinal plants. The average pre-test score obtained was 89.47, while the average post-test score was 93.52. The range of pre-test scores given before the material was presented and the post-test scores given after the presentation increased by 4.05. This indicates an increase in the knowledge of Dasa Wisma mothers regarding the types of medicinal plants in the family, as well as their processing and use. This community service effectively increased the knowledge of Dasa Wisma mothers about medicinal plants, how to process them, and their uses.